2008
DOI: 10.1002/mc.20478
|View full text |Cite
|
Sign up to set email alerts
|

Association between polymorphisms in the GSTA4 gene and risk of lung cancer: A case–control study in a Southeastern Chinese population

Abstract: GST Alpha 4 (GSTA4) has an important role in the protection against oxidative stress induced by carcinogens such as tobacco smoke. However, few studies investigated the association between GSTA4 polymorphisms and lung cancer risk. We genotyped three selected GSTA4 SNPs (rs182623 - 1718:T > A, rs3798804 + 5034:G > A and rs316141 + 13984:C > T) in a case-control study of 500 lung cancer patients and 517 cancer-free controls and evaluated the association between these SNPs and risk of lung cancer in this Han Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…On the other hand, genetic polymorphism of GST may affect gene expression if the mutation is located in the promoter region. Qian et al [37] studied single nucleotide polymorphisms (SNPs) of GSTA4, another GST that accepts HNE as a substrate [38]. Qian et al [37] found that the presence of genotypes TA and AA at locus-1718 of GSTA4 was associated with a 37 % significantly decreased risk of lung cancer compared to the TT genotype.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, genetic polymorphism of GST may affect gene expression if the mutation is located in the promoter region. Qian et al [37] studied single nucleotide polymorphisms (SNPs) of GSTA4, another GST that accepts HNE as a substrate [38]. Qian et al [37] found that the presence of genotypes TA and AA at locus-1718 of GSTA4 was associated with a 37 % significantly decreased risk of lung cancer compared to the TT genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Qian et al [37] studied single nucleotide polymorphisms (SNPs) of GSTA4, another GST that accepts HNE as a substrate [38]. Qian et al [37] found that the presence of genotypes TA and AA at locus-1718 of GSTA4 was associated with a 37 % significantly decreased risk of lung cancer compared to the TT genotype. The authors suggested that the TA and AA genotypes, with the SNP in the promoter region, may have increased GSTA4 expression and thus greater capacity to detoxify HNE as compared to the TT genotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, while rat Gsta4 is only 60% homologous with human GSTA4, the two enzymes have similar catalytic affinity to HNE ( 9 ), making it a valuable experimental target. Genetic associations have been made between GSTA4 mutations and risk for certain types of cancer ( 15 , 16 ), but not much is known about the role of GSTA4 in PD. However, HNE has been shown to be significantly elevated in PD brains ( 17 19 ), suggesting that GSTA4 is somehow affected and could be a key player in the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, certain Gsta4 polymorphisms increase the risk to develop melanoma and hepatocellular and lung cancer (1,28,32). In CNS diseases there are some indications that a Gstm1 null and a Gstm3 polymorphism increase the risk for PD and AD, respectively (23,30).…”
Section: Al Nimer Et Almentioning
confidence: 99%